Decision-making in international business - Buckley, Peter; Casson, Mark (Journal of International Business Studies, 2019)
This paper builds on preceding papers. It distinguishes three domains of international business theory: the boundaries of the multinational enterprise, the external environment of the enterprise and its internal structure. The central concern of internalisation theory is the boundaries of the firm. Any general theory of international business must also analyse the external environment and internal structure. Competition dominates the external environment while co-operation dominates internal structure. Different models of decision-making are required for each. Different theories of decision-making must therefore be integrated in order to transform internalisation theory into a general theory of international business. This paper examines how this can be done.